The market for fake observations - Kjell Arne Brekke; Tore Nilsen (University of Oslo, Department of Economics, 2011)
We show how increased competition in a media market may have implications for the competition between firms that are advertising in that medium. We apply a simple model of a product market with network externalities where firms buy advertising space in a media market and find that there is more entry in the product market, the more competitive the media market is. The paper is the first combining a study of media markets with a behavioral foundation of how advertising affects the demand for the advertised products.
Keywords: L82; M37; 330; Advertising; Media Market; Availability Heuristic; Network Externalities; Werbung; Medienmarkt; Preiswettbewerb; Theorie